YIELD OF INTERCROPPED LETTUCE AND CUCUMBER AS A FUNCTION OF POPULATION DENSITY AND CROPPING SEASON - Cecilio Filho, Arthur Bernardes [UNESP]; Alves Rezende, Braulio Luciano; Dutra, Alexson Filgueiras [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2019)
The possibility of increasing vegetable production per unit area is one of the advantages of the intercropping system. However, there is a lack of information about the effect of climatic factors and the management of different species on the viability of this production system. To this end, four experiments were carried out to evaluate the yield of intercropped lettuce and cucumber as a function of cropping season, cucumber population density, and lettuce transplanting time. Each experiment was conducted in a randomized block design with nine treatments arranged in a 2 x 4 + 1 factorial scheme, corresponding to two cropping systems (intercropping and monoculture), four transplanting times of 'Lucy Brown' lettuce (0, 10, 20, and 30 days after cucumber transplanting), and 'Hokushin' cucumber monoculture. The experiments were carried out in two seasons (August to November and February to May) and with two cucumber population densities (1.1 and 2.2 plants m(-2)). Total and commercial cucumber yields were not influenced by the presence of lettuce. However, regardless of cropping season, the presence of cucumber affected lettuce yield, with later transplanting corresponding to greater negative impact. Lettuce intercropped with cucumber at a density of 2.2 plants m-2 and grown from February to May did not reach commercial quality. The greatest efficiency of lettuce and cucumber intercropping was obtained by transplanting the two species on the same day in August, with cucumber at a density of 1.1 plants m(-2).
Keywords: Lactuca sativa L.; Cucumis sativus L.; Cropping systems; Transplanting time; Protected cultivation